Comment on 'An efficient code to solve the Kepler equation: elliptic case'. Issue 2 (24th June 2021) - Tommasini, D; Olivieri, D N
ABSTRACT: In a recent MNRAS article, Raposo-Pulido and Pelaez (RPP) designed a scheme for obtaining very close seeds for solving the elliptic Kepler equation with the classical and modified Newton–Raphson methods. This implied an important reduction in the number of iterations needed to reach a given accuracy. However, RPP also made strong claims about the errors of their method that are incorrect. In particular, they claim that their accuracy can always reach the level of ∼5ε, where ε is the machine epsilon (e.g. ε = 2.2 × 10 −16 in double precision), and that this result is attained for all values of the eccentricity e < 1 and the mean anomaly M ∈ [0, π], including for e and M that are arbitrarily close to 1 and 0, respectively. However, we demonstrate both numerically and analytically that any implementation of the classical or modified Newton–Raphson methods for Kepler's equation, including those described by RPP, has a limiting accuracy of the order of ε /2(1-e) . Therefore the errors of these implementations diverge in the limit e → 1, and differ dramatically from the incorrect results given by RPP. Despite these shortcomings, the RPP method can provide a very efficient option for reaching such limiting accuracy. We also provide a limit that is valid for the accuracy of any algorithm for solving Kepler equation, including schemes like bisection that do not use derivatives. Moreover, similar results are also demonstrated for the hyperbolic Kepler equation. The methods described in this work can provide guidelines for designing more accurate solutions of the elliptic and hyperbolic Kepler equations.